The Role of Teachers in Shaping Religious Character in Early Childhood through the Habituation Method at Al-Mumtaz IT Kindergarten, Pontianak City - Aisyah, Siti; Halida; Lukmanulhakim (Journal of Early Childhood Development and Education, 2024)
This research aims to describe and obtain information abaout the role of teachers in forming, religious character in early childhood through methods habituation at Al-Mumtaz IT Kindergarten Pontianak City. The benefits of this research are increase insight and knowledge abaout the inportance of the teacher’s role in shaping religious character through the habituation method. The participants in this research collects information regarding the role of teachers in forming religious character in early childood through habituation method. The participants in this research were 3 theacers who taught at Al-Mumtaz IT Kindergarten groups B2, B4 and B7.Data collection techniques used in this research are obeservation, interviews and dokumentation. Analiyze the data in do, namely data collection (data collection), data display (data persentation) and conclusion drawing (data conclusion). Technique checking the validity of the data used is triangulation, research results thourgh obervations, interviews and documentation show that the roles used by teachers in the formation of religious character through habituation methods in early childood in Kindergaten IT Al-Mumtaz PontianakCity, namely by using the role of teacher mentor, facilitator, and motivator, in farming religious character in children through the habituation method. This role has been carried out effectively.